The impact of comics on knowledge, attitude and behavioural intentions related to wind energy. Issue 4 (1st October 2016) - Rodriguez, Lulu; Lin, Xiao
Abstract: This study compares two modes of visually presenting information about wind energy – one using photographs and the other using cartoons – on audience's knowledge, attitudes and behavioural intentions. In an online experiment, participants were randomly assigned to the two treatments. Results indicate no significant difference between the two groups in terms of knowledge and attitudes, but those shown in the comics version showed stronger intentions to support wind energy than those shown as photos. Those exposed to the comics-aided brochure found it more informative, interesting and cognitively engaging. Those who saw the photo version found the brochure more credible.